Low Dose of Pizotifen in Migraine Prevention: A Comparison with Topiramate (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Background & Objective: Pizotifen is an alternative option for prophylactic treatment of migraine headache. This study aims to compare the efficacy and safety of pizotifen with topiramate; one of the most-widely used drugs in migraine prevention. Methods: This was a single blind, randomized, parallel-group study. After a 4-week baseline evaluation, patients with episodic migraine were randomly assigned to get either to piramate or pizotifen for a period of 12 weeks. Patients were asked to fill a headache diary through the study. Headache characteristics and the possible side effects were evaluated throughout and at the end of trial. Results: Sixty patients aged 20 to 49 were recruited to the study. With both drugs, the frequency, intensity and duration of headaches were significantly reduced (p < 0.05). Except for headache duration, pizotifen was significantly superior to  topiramate in the headache parameters assessed. Total reported side effects were initially higher inpatients who received pizotifen (37 vs. 22; P= 0.038); however, persistent side effects were lower for pizotifen (6 vs. 10; P= 0.22).Conclusions: The results of this study suggest that pizotifen is a safe and effective drug in migraine prevention.